Melhoria contínua e desenvolvimento de kpi's na indústria de cablagens metálicas - Pereira, João Manuel Correia Lopes (2018)
The automotive industry, and in particular the production of components for the automotive industry, is one of the most demanding sectors of the global market, with the different companies needing to continuously be evolving and quickly adapt themselves. The response capacity and flexibility of companies represent a key factor for their success. Through the last decades, a growing concern with the creation of a mentality of excellence and vision of continuous improvement, with actuation on the optimization of equipment, processes, tools and people skills, has expressed its efforts in terms of cost reduction and increased competitiveness. This dissertation was developed during an internship period, in an industrial context, carried out in the company Fico Cables, producer of components as metallic cables and comfort systems for the automotive industry. This work was incorporated in the Production and Continuous Improvement departments. The developed work focused on the optimization of a specific assembly line, with the support of various tools included in the Lean Thinking and Lean Manufacturing concepts, with the identification and elimination of different types of wastes (mudas) and the balancing of operations between the different workstations in order to increase the global efficiency and productivity. A f Through the application of a different methodology, as Six Sigma, it was carried out a different improvement project with the aim to reduce the quantity of scrap on the most critical sector of Fico Cables, and the achievement of a better comprehension of the flows, process characteristics and different variables associated to the scrap production. In every company, having information by itself is not advantageous if it is not properly handled and filtered in order to direct efforts towards the real and most critical problems. In this way, it was also part of the developed work, the implementation and improvement of a problemsolving A3 methodology to manage different production-related Key Performance Indicators (KPI), with the adequate stratification of information, improvement actions plan and validation of results. The realization of these improvement projects allowed the company to achieve relevant productivity gains on the assembly line, a solid path to achieve the purposed goals on the diminution of the quantity of scrap and a better management of KPIs information.